2009
DOI: 10.1063/1.3120486
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fluid-solid phase transition of hard-sphere fluids in cylindrical pore via molecular dynamics simulation

Abstract: Articles you may be interested inThe isotropic-nematic phase transition of tangent hard-sphere chain fluids-Pure components J. Chem. Phys. 139, 034505 (2013) Equation of state and structure of hard-sphere fluids confined in a cylindrical hard pore were investigated at the vicinity of fluid-solid transition via molecular dynamics simulation. By constructing artificial closed-packed structures in a cylindrical pore, we explicitly capture the fluid-solid phase transition and coexistence for the pore diameters fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…An important theoretical feature of q1D systems is that they do not present genuine phase transitions, as long as particle interactions remain short-ranged [6,26,27]. As confinement weakens, these systems nonetheless exhibit a complex ordering behaviour characterized by relatively sharp structural crossovers [28][29][30][31][32][33][34][35][36][37]. A number of studies have shown that at finite pressure, these crossovers are accompanied with non-monotonic and non-smooth changes to the correlation length [10,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…An important theoretical feature of q1D systems is that they do not present genuine phase transitions, as long as particle interactions remain short-ranged [6,26,27]. As confinement weakens, these systems nonetheless exhibit a complex ordering behaviour characterized by relatively sharp structural crossovers [28][29][30][31][32][33][34][35][36][37]. A number of studies have shown that at finite pressure, these crossovers are accompanied with non-monotonic and non-smooth changes to the correlation length [10,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…In bulk, the constant pressure region ͑i.e., fluidsolid phase transition͒ is unobtainable for the hard sphere system by using the generic NVT MD simulation, however, the same method has shown its capability to capture the emergence of the phase transition for the hard sphere fluid confined in the cylindrical pore without any extra recipe in simulation technique. 15 In this study, although the occurrence of the phase transition has been assessed even with coinciding variation of calculated order parameters, we alert that one must not think of this particular phase transition as the firstorder transition without a proof of thermodynamic phase equilibria. The absence of the driving force of the phase equilibria or the discontinuity of the free energy.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study 15 indicates a strong dependence of the fluid-solid coexistence of hard sphere fluids on the pore size and it is expected that both the range of interaction and pore size have significant effects to the fluid-solid behavior. Another important factor in studying the behavior of model fluids is the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are a number of computersimulation studies demonstrating that freezing/melting may occur continuously as well as discontinuously in quasi-one-and quasi-two-dimensional systems. [10][11][12][13][14] Very recently, we have provided compelling evidence of the solid-liquid critical phenomena, and a molecular-level mechanism of the continuous melting, for a model of water confined in quasi-one-dimensional hydrophobic nanopores. 15 There remain unresolved questions as regards the solidliquid critical phenomena found in molecular simulations, and one of the important issues is what makes the intriguing phenomena possible: whether or not the orientation-dependent intermolecular interaction such as hydrogen bonding is necessary, or the external field that confines molecules in a narrow cylinder or slit is sufficient.…”
Section: Introductionmentioning
confidence: 99%